Analisis Sifat Fisik dan Mekanik Plastik Biodegradable Berbahan Dasar Pati Singkong dengan Penambahan Plasticizer Sorbitol - Qisty Annisa, Netia; Santosa, Santosa; Ismanto, Sahadi Didi (Departmen Of Agro-industrial Technology, Universitas Andalas, 2024)
Biodegradable plastic is a type of plastic that undergoes biodegradation at a significantly faster rate than conventional plastic and is composed of renewable raw materials. The primary raw material used in the production of biodegradable plastic is polysaccharides derived from starch that has undergone gelatinization. In this study, cassava starch was selected as the base material. The use of starch as the main component in biodegradable plastic production is a viable alternative due to its abundant availability, ease of decomposition, and relatively low cost. However, starch-based biodegradable plastic has a major drawback—its low mechanical strength. To address this limitation, plasticizers and other additives are incorporated to enhance the elasticity of the resulting plastic. This study aims to analyze the effect of sorbitol plasticizer concentration on the physical and mechanical properties of biodegradable plastic, determine the optimal concentration of sorbitol plasticizer to achieve the best biodegradable plastic properties, and assess the added value of the resulting biodegradable plastic. The research methodology employed a Completely Randomized Design (CRD) with five treatments and three replications. If significant differences were observed, further analysis was conducted using Duncan’s New Multiple Range Test (DNMRT) at a 5% significance level. The findings indicate that the addition of sorbitol plasticizer significantly influences the physical and mechanical properties of biodegradable plastic. The optimal treatment was observed with a 40% sorbitol plasticizer concentration, yielding an average thickness of 0.23 mm, a water vapor transmission rate of 11.45 g/m²·h, a biodegradability rate of 62.12% over two weeks, water resistance of 35.47%, tensile strength of 0.56 MPa, elongation of 23.98%, and elasticity of 0.03 MPa. The added value obtained was Rp 90,376/kg, with a value-added ratio of 63.11%.